Dissolution Profile Study and Uniformity of Dosage Units Test for Various Manufacturers of "Captopril" Drugs from the Russian Market - D. Yu. Grebenkin; A. V. Ryabova; A. M. Kuramshina; I. V. Kislyakov; E. D. Zhukova (Разработка и регистрация лекарственных средств, 2023)
Introduction. As part of a comparative assessment of drugs quality available on the Russian market a dissolution profile studies and uniformity of dosage units test was conducted for various manufacturers of "Captopril" drugs. Drug release studies in three dissolution media (0.1 M hydrochloric acid, acetate buffer pH 4.5, phosphate buffer pH 6.8) with sampling at 0, 5, 10, 15, 20, 30 min and analysis using UV/Vis spectrophotometer at 212 nm were conducted. Dissolution kinetics was compared based on calculation of the similarity factor f2 and the values of relative standard deviations. Uniformity of dosage units test of scored tablets were evaluated based on HPLC-UV analysis and AV factor calculation.Aim. The purpose of this study was a comparative evaluation of "Captopril" drugs from various manufacturers on the Russian market based on dissolution profile studies and uniformity of dosage units test of scored tablets in order to assess the quality of the tablets.Materials and methods. To prove the dissolution profile studies DT 827/1000 tester (ERWEKA GmbH, Germany) was applied. Each drug in three dissolution media in 12 replicates for each dissolution medium was analyzed. The selected samples were analyzed on a UV 1800 UV spectrophotometer (Shimadzu, Japan) at a of 212 nm. In uniformity of dosage units test of scored tablets each tablet was divided according to the applied mark. Sample preparation was carried out in accordance with a validated method and samples were analyzed by HPLC-UV using Agilent 1260 (Agilent Technologies, США).Results and discussion. Based on the results of dissolution profile studies and calculations of the similarity factors and values of the relative standard deviation it can be concluded that the dissolution kinetics for drug no. 4, drug no. 5, drug no. 6 are not equivalent in comparison with the reference drug. During the uniformity of dosage units test of scored tablets, no deviations were found in accordance with the requirements of the RF Pharmacopoeia OFS.1.4.2.0008.18 "Uniformity of dosing" and the EAEU Pharmacopoeia OFS.2.1.9.14 "Uniformity of Dosed Units".Conclusion. The conducted dissolution profile studies and uniformity of dosage for scored tablets of Captopril drugs show the example of possibility to identify potential problems with drugs quality presented on the Russian market and as a result improve and maintain quality assurance of drugs for the national healthcare system.